Residential Environment and Parental Lifestyle as Risk Factors of The Co-Occurrence of Cleft Lip and Palate Birth Defect Cases in Indonesia - Intan Nur’azizah Rahman; Rinaldy Jose Nathanael; Imtiyaz Olaf Jatmy; Taqya Izdihar Muhanandi; Ida Latifah; Andi Tajrin; Ikeu Tanziha; Shinta Silvia; Farah Asnely Putri; Ida Ayu Astuti; Asri Arumsari; Utriweni Mukhaiyar; Katharina Oginawati; Nurul Fahimah (Journal of Multidisciplinary Applied Natural Science, 2025)
Cleft lip and palate (CLP) are multifactorial birth defects, and the etiology behind their occurrence remains insufficiently understood. This case-control study aimed to investigate the association between residential environmental factors, parental lifestyle, and the risk of CLP in Indonesia. A total of 213 participants from 14 provinces were selected using stratified random sampling. Multivariable logistic regression was employed to determine the odds ratios (ORs) with 95% confidence intervals (CIs) for each risk factor. The study identified significant associations between several residential environmental factors and CLP. Proper kitchen ventilation was found to be protective (OR = 0.245, 95% CI: 0.096–0.624, p = 0.003), while proximity to industrial sites significantly increased the risk (OR = 3.595, 95% CI: 1.029–12.558, p = 0.045). Additionally, using treated drinking water showed a protective effect (OR = 0.39, 95% CI: 0.16–0.95, p = 0.038), whereas concerns about water sources displayed a marginally significant risk increase (OR = 2.841, 95% CI: 0.876–9.211, p = 0.082). Regarding parental lifestyle factors, maternal active smoking exhibited a marginal protective association (OR = 0.052, 95% CI: 0.002–1.09, p = 0.057), while paternal passive smoking presented a marginally significant risk (OR = 2.309, 95% CI: 0.897–5.942, p = 0.083). Furthermore, paternal radiation exposure was associated with an elevated risk of CLP (OR = 3.489, 95% CI: 0.828–14.703, p = 0.089). These findings highlight the need for targeted public health interventions to mitigate environmental exposures and promote safer parental lifestyle behaviors in Indonesia.